AN INTERCULTURAL TECHNOLOGICAL ELEMENT FOR THE LEARNING OF PROPORTIONALITY IN A RESERVATION OF THE EMBERÃ-CHAMÃ-COLOMBIAN ETHNIC GROUP - Luis Hernando Carmona-RamÃrez; Jorge Luis Bedoya-Serrano (Ethnomathematics Journal, 2023)
The panorama of ethno-education is compromising for the 115 native indigenous ethnic groups from Colombia, bearing in mind that some educational institutions have not advanced in the incorporation of their own knowledge in their intercultural curricula. The aim of this qualitative tradition (Educational Action Research) study was to implement a bilingual (Ebera-bedea/Spanish) Intercultural Technological Element (ITE) by using Geogebra in order to teach the concept of proportionality in an indigenous reservation of the ethnic group EmberÃ¡-ChamÃ. 13 students of basic secondary education belonging to ethnic group were included. Firstly, a diagnostic evaluation was performed to assess the initial knowledge of the students about the concept of proportionality in their own native language. Then the ITE was designed and applied to the students. The students were evaluated on three aspects (1) on their own knowledge, (2) on the affective and emotional aspect and on (3) their conceptions. In general, the students were able to contemplate the relationship between the topic developed (proportionality) and the activities of the culture with a reception of 77%. Regarding the emotional aspect 62% of the students see the solution of the guides as favorable since it promotes individual work as well as responsibility, and the other 38% perceive it moderately. On the other hand, the worldview and cosmogony conceptions were achieved in the 84% of the students.